2012
DOI: 10.2220/biomedres.33.153
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of distention-induced ATP release from urothelium by the adenylyl cyclase-cyclic AMP pathway

Abstract: Distention of the bladder during urine storage induces ATP release from urothelium, thereby facilitating transmission of visceral sensory signals to afferent nerve fibers. An excess of urothelial ATP release was found in interstitial cystitis, a condition accompanied by hyperesthesia of the urinary bladder; it remains unclear which signals are involved in this upregulation. The present study demonstrated that the adenylyl cyclase pathway enhances distention-induced ATP release in mouse bladder. In the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
3
8
1
Order By: Relevance
“…Urothelial cyclic AMP is involved in the afferent component of micturition by facilitating ATP release, which in turn activates bladder reflexes and enhances bladder sensation, particularly under pathological conditions. ATP is known to play a major role in the afferent sensory component of the voiding cycle by binding to its receptor P2X3 21 . The reduced intracellular and extracellular contents of ATP in urothelial cells incubated with succinate, as demonstrated in this study, might explain at least in part the relaxation observed.…”
Section: Discussionsupporting
confidence: 63%
“…Urothelial cyclic AMP is involved in the afferent component of micturition by facilitating ATP release, which in turn activates bladder reflexes and enhances bladder sensation, particularly under pathological conditions. ATP is known to play a major role in the afferent sensory component of the voiding cycle by binding to its receptor P2X3 21 . The reduced intracellular and extracellular contents of ATP in urothelial cells incubated with succinate, as demonstrated in this study, might explain at least in part the relaxation observed.…”
Section: Discussionsupporting
confidence: 63%
“…The present study demonstrated that pBOO increases al change caused by pBOO released ATP from serosal side of the bladder. The release of ATP from the urothelium upon physical distention is a well-known occurrence (22,23). In our study, the change in the ATP increment caused by physical distention (10 and 30 cmH 2 O) was not significant between the control and pBOO rat urothelium.…”
Section: Discussioncontrasting
confidence: 45%
“…ATP is released from the pelvic postganglionic nerve ending with acetylcholine and activates the P2Y receptors in the bladder smooth muscle to lead the initial bladder contraction in the process of micturition (3,6,21). ATP is also released from urothelial cells during bladder stretching (2,8,29) or upon activation of the transient receptor potential (TRP) V1 channel, muscarinic acetylcholine receptors, or 5HT receptors, and activates P2X receptors on the afferent nerve terminals (2,23). These P2X receptors can elicit the activity of the afferent nerves during the storage of urine and most likely trigger the micturition reflex (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory effect of 5-HT 1D on ATP release could be achieved by suppressing cAMP, because the adenylyl cyclase-cAMP pathway facilitates distention-evoked ATP release from the urothelium [41]. These data suggest that urothelial 5-HT 1D could inhibit the micturition reflex by depressing ATP release.…”
Section: Function In the Urotheliummentioning
confidence: 82%